Treatment of wrist stiffness through posture orthosis and active exercise: A case report - Paolo Boccolari; Mario Lando; Lucia Zingarello; Leonardo Monzani Vecchi; Roberto Tedeschi; Danilo Donati (Trauma Case Reports)
Introduction: Wrist fractures, particularly the distal radius, can result in significant stiffness and hand dysfunction if not mobilized early. The variable immobilization period post-fracture depends on fracture type, location, stability, and surgical intervention. Inadequate early mobilization typically leads to structured stiffness, influenced by patient health, injury mechanism, joint surface involvement, associated tissue injuries, and patient motivation. Case presentation: A 64-year-old female in good health suffered a distal radius fracture, treated with open reduction and internal fixation. A modified treatment plan, including custom orthosis and active wrist exercises, was initiated after the standard immobilization phase to enhance the range of motion while accommodating the patient's daily activities. Clinical discussion: The patient underwent 15 evaluations of active range of motion (AROM) using a goniometer, guided by the American Society of Hand Therapists. A Tissue Composition Analysis (TCA) was performed to guide the orthosis-treatment choice. Despite consistent improvement shown in AROM, it was inconclusive whether the modified treatment contributed significantly beyond the standard approach. Conclusions: While the patient's AROM improved, the treatment's effect on this single case cannot definitively confirm the efficacy of the modified approach. A more extensive study is necessary to evaluate the conservative treatment strategy's validity for such fractures in high-demand patients, considering the biomechanical complexity of the injury and the patient's professional needs.